Beyond "buy-in": designing citizen participation in water planning as research. (1st October 2016) - Hall, Damon M.; Gilbertz, Susan J.; Anderson, Matthew B.; Ward, Lucas C.
Abstract: In United States water resources management, water quantity planning (supply, availability, and use) fall within the domain of individual states. Because water is a shared resource held in trust for the use of a state's citizenry, its management obliges the involvement of water users. Under the above regime, states have much discretion concerning how to accomplish this. In state water planning, a variety of activities are considered stakeholder engagement. Natural resource management agencies often treat public participation as a chore for attaining legitimacy whose resources might be better used for technical aspects of planning. This paper details the public participation design for the 2015 Montana State Water Plan's Yellowstone Basin scoping phase. It argues that design of participatory practices is the key variable for successful participation. Stakeholders are experts whose knowledge can be incorporated into planning to inform priorities, corroborate biophysical data, and supply insights for communicating science and policy to citizens across specific localities. We argue that stakeholder engagement in water resources planning should be treated as research for the purposes of gathering and organizing social and biophysical truths. Through participant data approaches, citizen comments as data can improve the informational basis of planning and relational aspects. Public buy-in (legitimation) is not the objective of stakeholder participation; however, it can be a by-product of good design which suits the context and effectively uses citizen input to improve decision making. Using experience from basin-scale citizen advisory committees, this essay offers recommendations for water planners to design productive public engagement practices. Highlights: Stakeholder buy-in is not the aim but a by-product of sound engagement design. Effective public participation in water policy is treated as research. Via a participant data approach, we outline successful stakeholder engagement. Good design ensures citizens' comments are useful to and used within planning. We chronicle the Yellowstone Basin scoping for the 2015 Montana State Water Plan.